Pertanggung Jawaban Pelaku Tindak Pidana Pencurian Yang Dilakukan Anak Berdasarkan Krimilogogi - Prastyo, Indra (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to understand and analyze the provisions of theft crimes committed by children based on criminological theory. and to understand and analyze the legal responsibility of children who have committed theft crimes in the juvenile justice system in Indonesia. This type of research is normative legal research, also called doctrinal research, where the law is often conceptualized as what is written in legislation (law in books) or conceptualized as rules or norms that are benchmarks of human behavior that are considered appropriate. In this study, the approach to the problem used is a statutory approach (statue approach) carried out by examining all laws and regulations related to the legal issues handled. The results of this study are 1) Provisions of the Crime of Theft Committed by Children Based on the theory of Criminology Crime itself seen from the juridical concept, means human behavior that can be punished under criminal law. 2) The juridical liability of minors in the Criminal Code and the criminal liability of minors according to the 2012 Law on the SPPA Child Criminal Justice System, it is clear that minors who commit theft, will be processed according to the applicable provisions, namely by looking at the elements of the article charged, namely the article in the Criminal Code, namely Article 362, but the trial process is in accordance with what is regulated by Law Number 11 of 2012 concerning the Child Criminal Justice System.